Development and validation of a fast ultra‐high‐performance liquid chromatography tandem mass spectrometry method for determining carbonic anhydrase inhibitors and their metabolites in urine and hair. Issue 8 (16th July 2021) - Lo Faro, Alfredo Fabrizio; Tini, Anastasio; Gottardi, Massimo; Pirani, Filippo; Sirignano, Ascanio; Giorgetti, Raffaele; Busardò, Francesco Paolo
Abstract: A new, rapid, sensitive, and comprehensive ultra‐high‐performance liquid chromatography tandem mass spectrometry (UHPLC–MS/MS) method for quantifying diuretics (acetazolamide, brinzolamide, dorzolamide, and their metabolites) in human urine and hair was developed and fully validated. Twenty‐five milligrams of hair were incubated with 500‐μl M3® buffer reagent at 100°C for 1 h for complete digestion. After cooling, 1‐μl supernatant was injected onto chromatography system. Urine samples were simply diluted before injection. The chromatographic run time was short (8 min) through a column with a mobile phase gradient. The method was linear (determination coefficients always higher than 0.99) from limit of quantification (LOQ) to 500 ng/ml in urine and from LOQ to 10 ng/mg in hair. LOQs ranged from 0.07 to 1.16 ng/ml in urine and from 0.02 to 0.15 ng/mg in hair. No significant ion suppression due to matrix effect was observed, and process efficiency was always higher than 80%. Intra‐ and inter‐assay precision was lower than 15%. The suitability of the methods was tested with six urine and hair specimens from patients treated with acetazolamide, dorzolamide, or brinzolamide for ocular diseases or systemic hypertension. Average urine concentrations were 266.32 ng/ml for dorzolamide and 47.61 ng/ml for N ‐deethyl‐dorzolamide ( n  = 3), 109.27 ng/ml for brinzolamide and 1.02 ng/ml for O ‐desmethyl‐brinzolamide ( n  = 2), and finally, 12.63 ng/ml for acetazolamide. Average hair concentrations were 5.94 ng/mg for dorzolamide and 0.048 ng/mg for N ‐deethyl‐dorzolamide ( n  = 3), 3.26 ng/mg for brinzolamide ( n  = 2), and 2.3 ng/mg for acetazolamide ( n  = 1). The developed method was simple and fast both in the extraction procedures making it eligible in high‐throughput analysis for clinical forensic and doping purposes. Abstract : A new, rapid, sensitive, and comprehensive UHPLC–MS/MS method for determining acetazolamide, brinzolamide, dorzolamide, and their metabolites in human urine and hair was developed and fully validated.